Efeitos de uma intervenção comportamental sobre a adesão ao protocolo pré e pós-operatório de uma revisão da artroplastia de substituição total da articulação do quadril - Horta, Carolina Campos Machado Marques (2018)
Treatment adherence has become a recurrent debate and research topic during the last 40 years. Poor adhesion is one of the main reasons for unsatisfactory results in the treatment of a disease. One of the main problems found by health professionals in the area of hip orthopedy is the poor adhesion to the preoperative and postoperative protocols for the total hip joint replacement arthroplasty, which reduce the patient's quality of life and waste health resources. This study aimed to develop and evaluate a behavioral intervention to increase the adhesion to the preoperative and postoperative protocols for the total hip joint replacement arthroplasty addressed to a patient which presented poor adhesion to the protocol in his first surgery. We used: (a) two surveys: one to evaluate the adhesion of the patient to the protocols, and the other to verify if the patient knew how to detect and describe relevant signals that should be reported to health professionals after the surgery; (b) two logs: one to evaluate the answers given by the patient in face-to-face meetings, and the other to evaluate the verbal report about his behavior in the last 24 hours in phone interviews; (c) an educational booklet with written instructions and images to guide the patient on the appropriate behavior before and after the surgery; and (d) three videos with examples of the exercises that should be executed before and after the surgery and appropriate movements of the body. In the initial meeting with the patient, we evaluated whether he fulfilled all the criteria to participate in the study. Before the intervention the researcher evaluated which behaviors were already a part of the patient's behavioral repertoire. During the intervention, the researcher used several strategies to increase the probability of adhesion to the surgical protocol, including shaping, modeling, instructions and positive reinforcement, in face-to-face meetings and in telephone interviews. After the intervention, the researcher repeated the same steps carried in before the intervention, besides phone interviews. During this phase the patient also filled a survey similar to the one used in the initial meeting. The results showed that the intervention produced a positive effect on patient's adherence to the surgical protocols. After the study, the patient presented a more complete adhesion to the items in the protocol to which adhesion was initially only partial